Clinal polymorphism variation in the Booted Eagle Hieraaetus pennatus: the influence of climate during the breeding season. Issue 3 (3rd July 2019) - Bosch, Josep
ABSTRACT: Capsule: The existence of clinal variation in the colour polymorphism of the Booted Eagle Hieraaetus pennatus in its breeding area in the Palaearctic is probably caused by the influence of precipitation and the detectability of the two morphs in different light conditions. Aims: To test whether Booted Eagles shows clinal variation in colour polymorphism along its breeding range in the Palaearctic and to test if there was selective or/and environmental pressure in the polymorphism throughout its breeding range in the Palaearctic and South Africa. Methods: Published data were obtained on the proportion of colour morphs of seven study populations within the Palaearctic and South Africa, as well as those of 11 populations on the Iberian Peninsula, and the variation was examined in relation to longitude, latitude, and environmental and meteorological variables. Results: There was a strong relationship between the proportion of the dark morph and longitude from west to east. In the Palaearctic and South Africa, there was a strong positive relationship between the proportion of the dark morph and the amount of rainfall during the period of chick growth. Conclusion: There is clinal variation in colour polymorphism in the Booted Eagle. The variation is probably maintained by disruptive selection due to climatic factors such as rain and cloud cover, which influence the detectability of the different colour morphs to their prey.